Micrometric research results of vacuum dough divider components - E. G. Martynova; S. A. Velichko; A. V. Martynov (Advanced Engineering Research, 2019)
Introduction. Nowadays, vacuum-type dough dividers are used in industries with a production volume of up to 4,000 loaves per day. In the dough divider operation, due to wear of the working surfaces of the piston, chamber, and drum, the gap between them goes beyond the value equal to 50 microns, which provides vacuum in the suction chamber. As a result, the suction process becomes unstable; the dough divider disturbs the weight accuracy of bakery goods. Repair of such equipment is carried out mainly through a full or partial replacement of worn parts and assemblies with new ones. To increase their durability, there is a need to develop a new highly efficient technology with the restoration of worn part surfaces using the welding and surfacing methods.Materials and Methods. A new technique of determining the number of objects for research using the “STATISTICA” program is presented. Wear surfaces of the vacuum dough divider parts are determined.Research Results. Micrometric studies of the dough divider components were carried out. They showed the presence of appreciable size distortions due to the local wear of the working surfaces. In this case, a side gap between the suction chamber and the main piston and between the drum and the suction chamber is 6 times higher than the permissible one, and a vertical gap between the division box and the piston exceeds the permissible gap by more than 10 times. Wear of the working surfaces of the dough divider parts is local in nature, while the range of values is as follows: for the main piston, it is 10-200 microns; for the gaging piston, it is 250- 900 microns; for the suction chamber and division box, it is 300-400 microns; for the drum surfaces, it is 280-300 microns.Discussion and Conclusions. The conducted micrometric studies showed the presence of appreciable size distortions due to the local wear of the working surfaces. Based on the results obtained, it can be argued that the most productive and economically viable technique for the restoration of worn surfaces of dough divider parts is, for example, the electrospark machining.